Genotypic and Phenotypic Diversity of Endemic Golden Camellias Collected from the North of Vietnam - Van-Anh Le, T.; Mai Nga, T. P.; Nhi Nguyen, P.; Kieu-Oanh Nguyen, T.
Golden Camellias have recently been used as a food, cosmetic, and traditional medicine in China and Vietnam. Forty-two species have natural distribution in Vietnam, of which thirty-two species were considered endemic species of this country. The morphology of leaves and flowers of these species were similar; therefore, their taxonomic identification usually needed experts and the authentication has often been confused among species. Our study aims to describe the genetic diversity and the relationship of six species Camellia phanii, Camellia tamdaoensis, Camellia tienii, Camellia flava, Camellia petelotii and Camellia euphlebia by using three chloroplast DNA-barcodes: matK, rbcL and trnH-psbA. We also clarified the significant differences in anatomical characteristics of midvein and blade of their leaves, which suggested the possibility to use these criteria in taxonomy. In addition, preliminary chemical profiles of the methanolic extracts of leaves from six Golden Camellias such as total phenolic content (TPC), total flavonoid content (TFC), total anthocyanin content (TAC)and chlorogenic acids content (TCGAs)also showed the diversity among them. Interestingly, the discrimination on the catechins profile among six species followed the same tendency with the genetic distance on the phylogeny tree suggesting that catechins (i. e., discriminative catechins)can be biomarkers for the chemotaxonomy of these six Golden Camellias.
Keywords: TAC; TCGAS; TFC; TPC; GENETIC DIVERSITY; GOLDEN CAMELLIA; LEAF ANATOMY